2019
DOI: 10.13057/asianjagric/g020205
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of technical efficiency in cotton production in the southern cotton growing zone of Nigeria: A stochastic production frontier approach

Abstract: Abstract. Olatidoye MS, Alimi T, Akinola AA. 2018. Quality assessment of the physico-chemical properties of vermiwash produced from different sources during successive storage periods. Asian J Agric 2: 58-63. The study investigated on socio-economic factors and estimated the technical efficiency indices and factors influencing technical efficiency of the sampled cotton farmers in the Southern Cotton growing zone of Nigeria. A multistage sampling technique was employed to select a total sample of 300 cotton far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…But, and there is no significant yield difference between junior high school educated farmers and farmers with elementary school education. This result is in line with [12], [13] and [17] that education will affect the managerial ability of farmers so that it has a positive effect on yield.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…But, and there is no significant yield difference between junior high school educated farmers and farmers with elementary school education. This result is in line with [12], [13] and [17] that education will affect the managerial ability of farmers so that it has a positive effect on yield.…”
Section: Resultssupporting
confidence: 77%
“…Likewise, Alamsyah [11] found a significant difference between production and income earned by farmers at various levels of oil palm plantation management. While plantation management practices, plantation management is also strongly influenced by the characteristics of farmers, including age, experience, formal education [12]; [13], number of family members [12]; [13], membership in cooperatives and access to credit [13],…”
Section: Introductionmentioning
confidence: 99%
“…The situation remains so, partly because most farmers lack the technical knowledge, managerial ability and have failed to seek the counsels of experts which in turn limit their ability to maximize output that can translate into huge capital. This was further corroborated by the submissions of Akinola et al (2015) and Olatidoye et al (2018a), that one of the most serious constraints of agricultural growth in Nigeria is the inefficient use of productive resources and that considerable growth can be achieved by simply improving the level of efficiency in resource use.…”
Section: Introductionmentioning
confidence: 75%
“…It is a heavily built animal with round muzzle, small round ears, short tail and harsh bristly fur. Apart from being the most preferred, it is the most expensive bush meat in most West African countries, Nigeria inclusive [4]. It contributes to both local and foreign earnings in some of these countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that one of the most serious constraints of agricultural growth in Nigeria is the inefficient use of productive resources and that considerable growth can be achieved by simply improving the level of efficiency in resource use [7,8]. Studies conducted by Akinola et al [2] and Olatidoye et al [4] revealed that Grasscutter production in Southwest, Nigeria, is mainly at subsistence level and output is relatively low despite its relatively competitive prices in both local and international market. It is therefore obvious that with the ever increasing human population and obvious protein shortage in Africa, an understanding of the efficiency of Grasscutter production in Nigeria, is most opportune.…”
Section: Introductionmentioning
confidence: 99%